Local field enhancement at the core of cylindrical nanoinclusions embedded in a linear dielectric host matrix - Abbo, Y.A.; Mal'nev, V.N.; Ismail, A.A. (Condensed Matter Physics, 2016)
In this paper we have discussed theoretical concepts and presented numerical results of local field enhancement at the core of different assemblages of metal/dielectric cylindrical nanoinclusions embedded in a linear dielectric host matrix. The obtained results show that for a composite with metal coated inclusions there exist two peak values of the enhancement factor at two different resonant frequencies. The existence of the second maxima becomes more important for a larger volume fraction of the metal part of the inclusion. For dielectric coated metal core inclusions and pure metal inclusions there is only one resonant frequency and one peak value of the enhancement factor. The enhancement of an electromagnetic wave is promising for the existence of nonlinear optical phenomena such as optical bistability which is important in optical communication and in optical computing such as optical switch and memory elements.